Exploring why religious faith may distinguish faith‐based from non‐faith‐based NGOs: Theoretical insights from Cambodia. (5th September 2022) - Frame, John
Abstract: Faith‐based and non‐faith‐based non‐governmental organisations (NGOs) are significant service providers in the developing world, yet limited research has compared these organisations, especially in the context of Southeast Asia. This paper explores a theoretical concept related to why religious faith may distinguish Christian faith‐based organisations (FBOs) from non‐faith‐based NGOs. Qualitative data were analysed from 41 interviews across 13 Christian FBOs and 12 non‐faith‐based NGOs working with women and children in Cambodia who have been (or were at risk of being) sexually exploited, trafficked or involved in sex work. Faith was found to distinguish FBOs from non‐faith‐based NGOs in all four of the dimensions comparatively examined in the study: (1) goals and missions, (2) motivations, (3) approaches to care and (4) conceptions of success. It is argued that the contrasts between these two types of organisations, in terms of faith, are related to the combination of both the infusion of faith in FBOs and factors related to the development context in which these organisations worked, a theoretical concept posited as Context‐Infusion Convergence .